“And then the person sort of just drops off the radar…”: barriers in the transition from hospital to community-based care among survivors of intimate partner violence in Metropolitan Atlanta - Evans, Dabney P.; Pawcio, Jocelyn; Wyckoff, Kathryn; Wilkers, Lee (Frontiers in Public Health, 2024)
Introduction Hospitals and community-based organizations (CBOs) provide the service-base for survivors of intimate partner violence (IPV), particularly those in acute crisis. Both settings face discrete challenges in meeting survivors’ needs. In hospitals these challenges include the pressures of a fast-paced work setting, and a lack of trauma-informed and survivor-centered care. Connections to community care are often unmeasured, with relatively little known about best practices. Often IPV survivors who receive hospital care fail to connect with community-based services after discharge. Despite the critical role of CBOs in supporting IPV survivors, there is limited research examining the perspectives and insights of CBO staff on the challenges and opportunities for improving care coordination with hospitals. The purpose of this study was to address this knowledge gap by characterizing CBO staff perceptions of IPV care coordination between hospital and community-based organizations in Metropolitan Atlanta. Methods We used a qualitative study design to conduct a cross-sectional examination of the perceptions and experiences of staff working at CBOs serving IPV survivors in Metropolitan Atlanta, Georgia. The adapted in-depth interview (IDI) guide was used to explore: (1) IPV survivor experiences; (2) Survivors’ needs when transitioning from hospital to community-based care; (3) Barriers and facilitators to IPV care coordination; and (4) Ideas on how to improve care coordination. Data analysis consisted of a thematic analysis using MAXQDA Analytics Pro 2022. Results Participants (N = 14) included 13 women and one man who were staff of CBOs serving IPV survivors in Metropolitan Atlanta. CBO staff perceived that: (1) IPV survivors face individual-, organizational-, and systems-level barriers during help seeking and service provision; (2) Care coordination between hospitals and CBOs is limited due to siloed care provision; and (3) Care coordination can be improved through increased bidirectional efforts. Conclusion Our findings highlight the multi-level barriers IPV survivors face in accessing community-based care following medical care, the limitations of existing hospital-CBO coordination, and opportunities for improvement from the perspectives of CBO staff. Participants identified silos and inconsistent communication/relationships between hospital and CBOs as major barriers to care connections. They also suggested warm handoffs and a Family Justice Center to support care connection.